Lieutenant-General Arthur Dillon : Jacobite at the Regency court 1715 - 1725 - Geange, Kate Elizabeth (Trinity College (Dublin, Ireland). Department of History, 2015)
This doctoral thesis examines Jacobite affairs between 1715 and 1725 by means of the Jacobite service of French Lieutenant-General Arthur Dillon. It investigates Dillon’s various roles and principal relationships entailed by his post as Jacobite representative to the French court during those years. The primary objective is to determine the consequences of Dillon’s service on the Jacobite political network, as well as to explore the significance of issues which permeated his service, such as influence, patronage, allegiance, loyalty and identity, as they apply to current historiographical thought on Jacobite exile.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin